The Views Of The Indonesian Ulema Council Of North Sumatra Province On The Punishment Of Husbands Who Marry Without The Wife's Permission In The Criminal Code - Anshari Nasution, Muhammad Zaid; Tanjung, Dhiauddin; Syahmedi Siregar , Ramadhan (Journal of Law, Politic and Humanities, 2024)
This study aims to (1) find out the provisions of the punishment of husbands who marry without the wife's permission in the Criminal Code (2) find out the views of the Indonesian Ulema Council of North Sumatra Province on the punishment of husbands who marry without the wife's permission in the Criminal Code (3) the author's analysis of the views of the Indonesian Ulema Council of North Sumatra Province on the punishment of husbands who marry without the wife's permission in the Criminal Code. This research is designed with a qualitative method with the type of research of this thesis is field research. The result of the research is that a husband who marries without his wife's permission is a crime in the Criminal Code. In addition to being a crime, it is considered an unlawful act (wederrechtelijk) in the context of Criminal Law. The MUI of North Sumatra Province is of the view that the criminalization of husbands who marry without the wife's permission is permissible even though in Islam there is no sanction/punishment for husbands who marry siri (secretly) and without the knowledge of the wife. A husband who remarries without his wife's permission can cause more harm than good. The imposition of sanctions (punishment) is also permitted because it can be classified as Ta'zir and contains benefits because it is a policy to protect wives who feel harmed.